Analisis Kualitas Pelayanan Publik Di Kelurahan Setia Asih Kecamatan Tarumajaya - Muhamad Lutfi Maulana; Djuni Thamrin; Matdio Siahaan; Joseph Martinio Jocrien Renwarin; Hadita Hadita (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The aim of this research is to determine the quality of public services and the factors that influence public services in Setia Asih Village, Taruma Jaya District, Bekasi Regency. This research is qualitative descriptive research, namely research that aims to describe and describe events and phenomena that occur in the field and present data systematically, factually and accurately regarding facts or phenomena that occur in the field. Data collection techniques were carried out using observation, interviews and documentation techniques. The research informants in this study were 1 Public Service employee as a key informant, and approximately 17 community service users as supporting informants. Data analysis in this research uses three components consisting of data reduction, data presentation, and drawing conclusions.The results of the research show that the analysis of the quality of public services in Setia Asih Village, TarumaJaya District is by using 3 important aspects, namely (1) Accessibility (2) Service Quality (3) Community Satisfaction and the low quality of public services in Setia Asih Village, TarumaJaya District is caused by several existing indicators in dimensions, Reliability, and Emphaty have not been implemented in accordance with service standards. The indicators that are not yet in accordance with service standards are (1) the Reliability Dimension, namely the employee's lack of mastery in using service tools. (2) The empathy dimension, namely whether employees are less friendly in the service process or still appear indifferent.